BRAF mutation positive papillary thyroid carcinoma is less advanced when Hashimoto's thyroiditis lymphocytic infiltration is present. (1st April 2013) - Marotta, Vincenzo; Guerra, Anna; Zatelli, Maria C.; Uberti, Ettore Degli; Di Stasi, Vincenza; Faggiano, Antongiulio; Colao, Annamaria; Vitale, Mario
Summary: Background: Concomitant papillary thyroid cancer (PTC) and Hashimoto's thyroiditis (HT) is a frequent occurrence. Whether these two conditions are linked and whether PTC with concurrent HT has distinct clinicopathological characteristics are still debated issues. Lymphocytic infiltration is abundant in HT and might be relevant in the pathogenesis and progression of PTC. BRAF V600E mutation is associated with a more advanced PTC at diagnosis; however, its role in the clinicopathological characteristics of PTC with concurrent HT is unknown. Design and patients: We enrolled 146 patients with histological diagnosis of PTC. Microscopic assessment of histology samples was performed to identify the presence of lymphocytic infiltration. Detection of BRAF V600E was performed on cytology samples by both direct sequencing and pyrosequencing, and results were correlated with clinical parameters. Results: Concurrent HT lymphocytic infiltration was associated with the female gender, smaller tumour size, a less frequent extracapsular extension and a lower grade of TNM staging. BRAF V600E was more frequent in PTC with concomitant lymphocytic infiltration. In PTC harbouring BRAF V600E, concurrent lymphocytic infiltration was still associated with the female gender, a less frequent extracapsular extension and a lower TNM staging. Conclusions: These results suggest that lymphocytic infiltration of HT is a protective factor against PTC progression, and it is independent of BRAF mutational status.